2021
DOI: 10.1155/2021/2852661
|View full text |Cite|
|
Sign up to set email alerts
|

The Potential Mechanism of Exercise Combined with Natural Extracts to Prevent and Treat Postmenopausal Osteoporosis

Abstract: Postmenopausal osteoporosis (PMOP) is a systemic chronic bone metabolic disease caused by the imbalance between bone formation and bone resorption mediated by estrogen deficiency. Both exercise and natural extracts are safe and effective means to prevent and control PMOP. The additive effect of exercise synergy extract against PMOP may be no less than that of traditional medicine. However, the mechanism of action of this method has not been clarified in detail. A large number of studies have shown that the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Osteoporosis and its complications place a huge economic burden on society and, at the same time, pose an unprecedented challenge to the health system as the majority of patients with osteoporosis go untreated [ 14 ]. In addition, since the numb of drug treatments for osteoporosis has decreased as a side effect of drugs for osteoporosis, many women are looking for natural plant drugs as alternative therapy [ 1 ]. Olive oil is an important part of the Mediterranean diet, which is known for its protective effects on human health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis and its complications place a huge economic burden on society and, at the same time, pose an unprecedented challenge to the health system as the majority of patients with osteoporosis go untreated [ 14 ]. In addition, since the numb of drug treatments for osteoporosis has decreased as a side effect of drugs for osteoporosis, many women are looking for natural plant drugs as alternative therapy [ 1 ]. Olive oil is an important part of the Mediterranean diet, which is known for its protective effects on human health.…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal osteoporosis (PMOP) is a systemic disease in women, which is mainly manifested as the loss of bone mass and increased risk of bone mass caused by the significant decline of estrogen in the clinic [ 1 ]. According to relevant data, more than 200 million women worldwide have osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical signal transduction is also an indispensable part of the responsiveness of bone to exercise. It has been clear that cells involved in bone metabolism and the immune response both share the microenvironment and interact to affect the bone remodeling process [ 50 ]. In particular, T cells, B cells, and inflammatory cytokines are important regulatory factors in the interactions of bone-immune systems, among which the role of T cells is pivotal [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested exercise as a possible alternative for the treatment of liver disorders and metabolic diseases [ 8 ]. In addition, various studies suggested exercise combined with treatment using natural products [ 9 ]. Some researchers have reported the development of a sports drink containing a physiologically active substance that can increase the effectiveness of exercise performance.…”
Section: Introductionmentioning
confidence: 99%